Islamic Social Finance and Sustainable Development Goals: Evidence from Indonesia - Muh Hidayatullah Hidayatullah; Nanang Qosim (IJED: International Journal of Economy Development Research, 2026)
Islamic social finance has increasingly become an important instrument for supporting sustainable development, particularly in Muslim-majority countries such as Indonesia. This study aims to examine the role of Islamic social finance in contributing to the achievement of the Sustainable Development Goals (SDGs) in Indonesia. The main instruments discussed in this paper include zakat, infaq, sadaqah, waqf, and Islamic philanthropic funds. Using a qualitative descriptive approach based on literature review and policy analysis, this study explores how Islamic social finance supports poverty reduction, social welfare, financial inclusion, education, health, and community economic empowerment. The findings indicate that Islamic social finance has strong potential to contribute to several SDGs, especially SDG 1 on poverty alleviation, SDG 2 on zero hunger, SDG 3 on good health and well-being, SDG 4 on quality education, SDG 8 on decent work and economic growth, and SDG 10 on reduced inequalities. However, its implementation still faces challenges, including institutional fragmentation, limited digital integration, low public literacy, and the need for stronger governance and accountability. This study concludes that Islamic social finance can serve as a complementary development financing mechanism in Indonesia if supported by effective regulation, institutional collaboration, digital innovation, and transparent fund management.